Retinal Microvascular Signs and Incidence of Abdominal Aortic Aneurysm: the Atherosclerosis Risk in Communities (ARIC) Study - Folsom, Aaron R. (Ophthalmic Epidemiol, 2017)
PURPOSE: To test the hypothesis that retinal microvascular abnormalities known to predict other cardiovascular diseases are associated prospectively with risk of abdominal aortic aneurysm. The rationale is that aortic aneurysm involves small vessel pathology that parallels, to some degree, retinal vasculopathy. METHODS: In 1993–1995, the Atherosclerosis Risk in Communities (ARIC) Study, a prospective population-based cohort, took retinal photographs of a randomly selected eye of 10,911 ARIC participants (initial mean age 60 years). Staff centrally graded the photographs using central retinal arteriolar equivalent (CRAE) and central retinal venular equivalent (CRVE) indices. We followed participants for incidence of abdominal aortic aneurysm (n=378 events), measured via medical record linkage from 1993 −1995 through 2011. RESULTS: Wider venular diameters were associated with increased incidence of abdominal aortic aneurysm, with the hazard ratio (95% CI) being 1.61 (1.20, 2.16) for the highest versus lowest quartile of CRVE. However, adjustment for other abdominal aortic aneurysm risk factors, particularly smoking, eliminated the association of CRVE with abdominal aortic aneurysm. CRAE and frank retinopathy showed no association with abdominal aortic aneurysm incidence. CONCLUSION: This prospective study found that retinal vascular diameters and retinopathy are not associated with incidence of abdominal aortic aneurysm.